The Effect of Booklets on Husbands' Knowledge and Support Regarding Basic Immunization - Septia Sri Lestari; Desy Rosita; Emy Yulianti (MEDICA (International Medical Scientific Journal), 2026)
Complete basic immunization is a key strategy in strengthening children’s immunity, preventing the transmission of infectious diseases, and reducing morbidity and mortality. However, immunization coverage in Indonesia remains suboptimal, as evidenced by the large number of children who did not receive complete basic immunization between 2017 and 2021. In West Kalimantan, immunization coverage is still below the national target, with Pontianak City achieving only 55% of the 95% Universal Child Immunization (UCI) target and Kubu Raya Regency reaching 68.3% as of December 2023. This study aimed to analyze the effect of booklet media on husbands’ knowledge and support regarding basic immunization. A quantitative approach was employed using a quasi-experimental design with a one-group pretest–posttest format. The study involved 83 respondents selected through non-probability sampling. Data were analyzed using the paired sample t-test to assess differences before and after the intervention. The results showed a statistically significant increase in both knowledge and support among husbands after the booklet intervention (p < 0.05). These findings indicate that booklet-based education is effective in improving husbands’ understanding and involvement in supporting basic immunization. In conclusion, the use of booklet media significantly enhances husbands’ knowledge and support regarding complete basic immunization in the Kuala Mandor B Community Health Center area, Kubu Raya Regency.